Kinesio Taping Does Not Alter Quadriceps Isokinetic Strength and Power in Healthy Nonathletic Men: A Prospective Crossover Study. (24th December 2015) - Korman, Paweł; Straburzyńska-Lupa, Anna; Rutkowski, Radosław; Gruszczyński, Jakub; Lewandowski, Jacek; Straburzyński-Lupa, Marcin; Łochyński, Dawid
Abstract : Objectives . The effects of Kinesio Taping (KT) on muscular performance remain largely unclear. This study aimed to investigate the acute effects of KT on the maximum concentric and eccentric quadriceps isokinetic strength. Study Design . This is a single-blinded, placebo crossover, repeated measures study. Methods . Maximum isokinetic concentric/eccentric extension torque, work, and power were assessed by an isokinetic dynamometer without taping (NT) and with KT or placebo taping (PT) in 17 healthy young men. Repeated measures one-way analysis of variance (ANOVA) was used for statistical analyses. Results . Testing concentric contractions at 60°/s or 180°/s isokinetic speed, no significant differences in peak torque (Nm), total work (J), or mean power (W) were noted among the application modes under different conditions. Testing eccentric contractions at 30°/s or 60°/s isokinetic speed, no significant differences in mentioned parameters were noted, respectively. KT on the quadriceps neither decreased nor increased muscle strength in the participants. Conclusion . KT application onto the skin overlying the quadriceps muscle does not enhance the strength or power of knee extensors in healthy men.